Reactions and characterization of solids - Dann, Sandra E. ([S.l.] : Royal Society of Chemistry, 2002)
The last twenty years or so has seen a change in the perception of solid state chemistry, in particular the scientific significance of understanding the relationship between chemical structure and physical properties. As such, it now forms an important part of both mainstream chemistry and material science degrees. Reactions and Characterization of Solids is designed as an introductory text with plenty of illustrative examples to reinforce the essentials of the topic. In the first few chapters, the fundamental principles of elementary crystal chemistry are introduced, together with the principles of both preparing and characterizing materials in the solid state. Some elementary thermodynamics are also included at this stage to introduce the idea of bond strength as a method of determining and predicting compound stability. General physical properties such as electronic and magnetic behaviour are discussed, together with specific topics relating to solid state materials such as non-stoichiometry. Furthermore, several solid state materials are described in detail, relating the fundamental properties and structural behaviour covered throughout the book to real systems and working materials. Ideal for the needs of undergraduate chemistry students, Tutorial Chemistry Texts is a major series consisting of short, single topic or modular texts concentrating on the fundamental areas of chemistry taught in undergraduate science courses. Each book provides a concise account of the basic principles underlying a given subject, embodying an independent-learning philosophy and including worked examples.
Keywords: chemistry,Reactions,characterization of solids